Environmental, social, and governance (ESG) disclosure and its impact on effective tax rate (ETR) in Malaysia - Abd Hamid, Nadiah; Aisyah Mohamad Taib, Hakimah; Md. Noor, Rohaya; Shamsuddin, Roszilah; Yusop, Rohayu (International Journal of Engineering and Technology, 2018)
The disclosure of Environmental, Social, and Governance (ESG) practices has become the most recent trend in providing non-financial information regarding Corporate Social Responsibility (CSR) activities of the companies. There are many benefits associated with ESG disclosure including tax burdens reduction through the utilization of tax incentives, which resulting in low Effective Tax Rates (ETRs). In Malaysia, the ESG Index has been launched by Bursa Malaysia in December 2014 to measure the performance of Public Listed Companies (PLCs) demonstrating strong ESG practices. Therefore, the current study aims to examine the level of ESG disclosure among PLCs in Malaysia and its possible effect on ETR. The data from 34 PLCs in Malaysia has been gathered and analyzed using the descriptive, correlation, and regression analysis. Results found that all three dimensions of ESG disclosure are negatively correlated with ETR whereby only environmental disclosure significantly affect ETR. Thus, PLCs would benefit most from the environmental programmes in the form of tax savings, while low ETRs indicate the existence of aggressive tax planning activities.Â